Proteoliposome-incorporated seawater reverse osmosis polyamide membrane: is the aquaporin water channel effect in improving membrane performance overestimated? - Zhao, Yali (2022)
The water channel feature of the aquaporin (AQP) is considered to be the key in improving the permselectivity of AQP-based thin-film composite (TFC) polyamide (PA) membranes, yet much less attention has been paid to the physicochemical property changes of the PA layer induced by AQP-reconstituted proteoliposomes. This study systematically investigated the roles of proteoliposome constituents (liposome/detergent/AQP) in affecting the physicochemical properties and performance of the membranes. For the first time, we demonstrated that the constituents in the proteoliposome could facilitate the formation of a PA layer with enlarged protuberances and thinner crumples, resulting in a 79% increase in effective surface area and lowering of hydraulic resistance for filtration. These PA structural changes of the AQP-based membrane were found to contribute over 70% to the water permeability increase via comparing the separation performance of the membranes prepared with liposome, detergent, and proteoliposome, respectively, and one proteoliposome-ruptured membrane. The contribution from the AQP water channel feature was about 27% of water permeability increase in the current study, attributed to only ∼20% vesicle coverage in the PA matrix, and this contribution may be easily lost as a result of vesicle rupture during the real seawater reverse osmosis process. This study reveals that the changed morphology dominates the performance improvement of the AQP-based PA membrane and well explains why the actual AQP-based PA membranes cannot acquire the theoretical water/salt selectivity of a biomimetic AQP membrane, deepening our understanding of the AQP-based membranes.